Voices From The Displaced: A Focus Group Discussion With The Yemeni Women Refugees In Malaysia - Fatima Mohamed Al-Majdhoub; Azizah Hamzah; Fauziyah Hanim Abdul Ree; Mohd Yahya Mohamed Ariffin (Asian Scholars Network, 2024)
Non-Indexed Publication